Integrated production of chemicals and fuels in the pulp industry: techno-economic and environmental analysis of black liquor gasification-based processes. - Domingos, Meire Ellen Gorete Ribeiro (2022)
The pulp and paper sector is classified as an energy intensive activity and several efforts are being made to mitigate its atmospheric emissions, improve the recovery of residual heat and capitalize on its byproducts. The black liquor (BL) is a byproduct of the kraft pulping process, which contains more than half of the energy content in the total woody biomass fed to the process, thus, representing a key supply of renewable energy to the pulping process. The BL can be gasified and the syngas can be used to generate electricity or produce chemicals and biofuels, through the broader biorefinery concept. In this work, the conventional scenario of the BL use (i.e. concentration and combustion) is compared with the BL upgrading gasification process for different chemicals and fuels (namely, hydrogen, synthetic natural gas, methanol, dimethyl ether, ammonia, urea and nitric acid) production, in terms of economics, exergy efficiency and environmental impact. A combined energy integration and exergy analysis is used to identify the potential improvements that may remain hidden to the energy analysis alone, namely, the determination and mitigation of the process irreversibility. The chemical processes synthesis, modelling and simulation are performed by using Aspen Plus® software. Meanwhile, the determination of the minimum energy requirements and the solution of the energy integration problem is handled by the OSMOSE Lua platform. A sensitivity analysis of the variation of the INPV as a function of the carbon taxation (0-100 EUR/tCO2) and the interest rate (0-21%) is performed. Firstly, it is assumed that the present values of the feedstock and the products are constant. Next, the incremental financial analysis incorporates the uncertainty related to the acquisition and selling costs of the feedstock and fuels produced, when embedded in a volatile market, by using the Monte Carlo method. As a result, the exergy efficiencies of the conventional setup and the kraft pulp and the integrated plants average 40% and 43%, respectively; whereas the overall emission balance varies from 1.97 to -0.79 tCO2/tPulp, respectively. In anticipation of future carbon taxation scenarios, the incremental economic analysis found that the fuels and chemicals production route with partial electricity import may economically outperform the conventional kraft pulp mill for moderate carbon taxations (30-100 EUR/tCO2), depending on the interest rate adopted. These results reinforce the relevance of the electricity import from the Brazilian mix for pushing upwards the share of renewable energy resources in the production of traditionally fossil-based chemicals and fuels, which could be an important factor in favor to the exploration of integrated biorefineries.